A design approach for controlled blade-off in overspeeding turbines - Eryilmaz, Ibrahim; Pachidis, Vassilios (Elsevier, 2022)
Following a shaft failure or loss of load in a gas turbine engine, the turbine overspeeds due to the continuing expansion through the stage(s). The overspeed may result in hazardous conditions which have to be prevented. Several mitigation methods include the control system’s response by shutting the fuel flow, mechanical friction to reduce turbine acceleration, and blade release at a predetermined rotational speed. The release of the blades not only terminates the gas torque which accelerates the disk, but also increases the disk burst speed at reduced centrifugal load. In this manuscript, a design space exploration is presented to avoid disk burst by blade-off in a civil large turbofan engine through a parametric design of blade firtree and disk post system. The firtree design parameters used in the study are the contact angle between the blade firtree and the disk post, firtree bottom flank angle, firtree flank length and firtree thickness with respect to the disk post. The LS-DYNA finite element software was used in the simulations to generate possible failure scenarios. These were ‘disk burst’ and ‘blade-off’. Blade-off conditions manifested in two ways as a function of design parameters. The first type was blade release from serrations without disk post failure, and the second type was blade escape with disk post failure. Following the design space exploration, the effect of several design and material parameters on the design space was investigated. These parameters are; the contact friction coefficient between the blade firtree and disk post, firtree serration number, and the strain hardening behavior of the material.
Keywords: turbine overspeed; Blade-off; LS-DYNA; Firtree